Therapeutic potential of modified Yukgunja-tang (Liujunzi Decoction, Rikkunshito) as an adjuvant treatment for lung cancer: a systematic review and meta-analysis - Kang, Sung-Woo; Ha, Seojung; Kim, Kwan-Il; Jung, Hee-Jae; Lee, Beom-Joon (Frontiers in Pharmacology, 2025)
BackgroundYukgunja-tang (YGJT), also known as Liujunzi Decoction or Rikkunshito, is a traditional East Asian herbal formula widely used to manage symptoms associated with cancer and chemotherapy. This study aimed to systematically evaluate the efficacy and safety of modified YGJT combined with standard antitumor therapy in patients with lung cancer.MethodsA comprehensive search was conducted in 10 databases through March 2025. Randomized controlled trials comparing modified YGJT plus antitumor therapy versus antitumor therapy alone or placebo were included. Studies involving other herbal combinations or East Asian therapies were excluded. Risk of bias was assessed using the Cochrane Risk of Bias 2 tool. A random-effects model was used for meta-analysis.ResultsThirty-one trials involving 2,496 participants were included. Modified YGJT significantly improved the objective response rate (ORR; RR 1.69, 95% CI 1.41–2.04), disease control rate (DCR; RR 1.21, 95% CI 1.11–1.31), and Karnofsky Performance Status (KPS; RR 1.79, 95% CI 1.23–2.60; MD 8.62, 95% CI 3.86–13.38). Symptom relief was observed (RR 1.52, 95% CI 1.25–1.85; MD -10.87, 95% CI -12.51 to −9.22), along with improvements in immune markers (CD3+, CD4+, CD8+, CD4+/CD8+ ratio) and reductions in tumor markers (CEA, CYFRA 21-1, NSE, SCC, CA19-9) and adverse events (myelosuppression, leukopenia, gastrointestinal reactions).ConclusionModified YGJT may offer clinical benefits as an adjuvant to standard lung cancer therapy by improving treatment outcomes and reducing toxicity. Large-scale, high-quality trials are needed to confirm these findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024619038, identifier CRD42024619038.